Empirical evidence on real convergence across brazilian states - Notini, Hilton Hostalácio (2006)
This paper examines the real convergence hypothesis across Brazilian states. In order to test for the existence of income convergence the order of integration of real Gross State Product (GSP) per capita series is examined as well as their differences with respect to the São Paulo state which is used as a benchmark state. Both parametric and semiparametric methods are used and the results show that convergence is achieved in the cases of Alagoas, Amazonas, Bahia, Goiás, Mato Grosso, Minas Gerais, Pernambuco, Piauí, Rio Grande do Sul, Rio de Janeiro and Santa Catarina and convergence is weakly achieved in the cases of Ceará, Maranhão, Pará, Paraná and Sergipe .The states of Espírito Santo, Paraíba and Rio Grande do Norte show no convergence.